The Urgency of Digital Technology Transformation in the Arabic Language Education: Media and Learning Strategies: Pentingnya Transformasi Teknologi Digital dalam Pendidikan Bahasa Arab: Media dan Strategi Pembelajaran - Meila Weeke Alfulana; Umi Hanifah; AB. Aziz bin Sulaiman (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2025)
The digital era affects all aspects of human life, including education. Internet users in Indonesia reached 78.19% in 2023 and continue to grow every year. According to the Ministry of Religious Affairs, planning is needed from all sectors for Indonesia's digital aspirations in 2045. Education as a human competency development sector must be able to educate students to compete globally and meet professional needs. As an effort to realize this, of course, the transformation of digital technology in the learning process cannot be avoided. This research aims to find out how urgent digital transformation is in Arabic language learning media and strategies. The researcher used qualitative research methods with library data sources. Researchers conducted an in-depth study of the urgency of digital technology transformation in Arabic language learning media and strategies. The results of the study show that digital technology transformation is needed in the process of learning Arabic, especially in psycholinguistic and sociolinguistic aspects. Digital technology can encourage learning that is effective, efficient, easy, and unlimited in space and time. Keywords: Arabic Language Education, Curriculum, Digital Technology